Endophytic bacteria isolated from the medicinal plant kratom (Mitragyna speciosa): Morphological, biochemical, and molecular characteristics, and their potential use as plant growth promoters (Scientia Agropecuaria, 2026)
Endophytic bacteria live within and colonize plant tissues, forming symbiotic interactions that often enhance host growth, health, and stress tolerance without causing harm. This study aimed to isolate endophytic bacterial strains from the medicinal plant ‘kratom’ (Mitragyna speciosa), characterize their biological functions by analyzing morphological, biochemical, and molecular properties, and evaluate their plant growth-promoting potential. The research followed standard procedures for isolating and analyzing the production of plant growth-promoting compounds, including indole-3-acetic acid, 1-aminocyclopropane-1-carboxylate deaminase, siderophores, cellulase, nitrogen fixation, and phosphate solubilization, and for assessing their effects on soybean in planta, including bacterial root colonization and plant growth. Of the isolates tested by 16S rDNA sequencing, five were successfully identified, belonging to Chromobacterium alkanivorans (2), Bacillus methylotrophicus (1), Stenotrophomonas maltophilia (1), and Chromobacterium violaceum (1). Quantitative assays showed that the bacterial isolates produced 13.35 – 24.11 g mL-1 of indole acetic acid, 20.77 – 24.95 μg mL-1 of inorganic phosphate solubilization activity, 63.34 – 84.29 U mL-1 of acid phosphatase, and 2.92 – 4.86 U mL-1 of cellulase. Qualitative tests confirmed that each isolate produced siderophores, nitrogenase, 1-aminocyclopropane-1-carboxylate deaminase, indole acetic acid, cellulase, and both organic and inorganic phosphate solubilization. Greenhouse experiments demonstrated that all bacterial isolates promoted plant growth, increasing soybean shoot length by 17.71% to 54.17%, root length by 14.36% to 39.34%, and total dry weight by 2.24% to 56.71% compared to controls. These findings support the potential application of endophytes as biofertilizers in sustainable agriculture, highlighting their capacity as plant growth-promoting bacteria.